The Integration of Interactive and Collaborative Tools 2.0 in Websites of Micro and Small Enterprises - Domenico Consoli (International Journal of Economic Behavior, 2015)
Nowadays also micro and small companies use interactive web sites that integrate some tools 2.0 (chat, blogs, forums, ...) and links to social networks, such as Facebook and Twitter, to interface with the external environment. By these new tools companies can interacts with all stakeholders of the supply chain and in particular with customers to improve their products/services. In this way between customers and company a bidirectional channel is established and a process of co-creation and co-production of products/services is stimulated. Small enterprises should take advantage using these technological channels to increase the competitiveness. In this paper we analyse the state of the art about the use of interactive and collaborative tools in websites of micro and small companies that have introduced some experimentations in this direction. The analysis is oriented to understand if entrepreneurs or managers think that these new digital channels are important in reaching business goals.